Testing the Female Underperformance Hypothesis - Magnus Henrekson; Anita Du Rietz (The Research Institute of Industrial Economics (IUI), 1999)
Most previous studies have found evidence at the aggregate level that female entrepreneurs underperform relative to their male counterparts. This study conducts a comprehensive test of this finding. The test is conducted on a large Swedish sample of 4200 entrepreneurs (405 females) with 1 to 20 employees in all sectors of the economy. Our study confirms the results of several previous studies that female entrepreneurs tend to underperform relative to men when the data is examined at the most aggregate level. At the same time our data reveals sharp structural differences between male and female entrepreneurs. In an extensive multivariate regression with a large number of controls it turns out that female underperformance disappears for three out of four performance variables. The only exception is sales. No gender difference is found for profitability. A more detailed analysis reveals that the evidence of female underperformance is much weaker in larger firms and nonexistent in firms with only one employee. If it is true that female entreprenurs on average have weaker preferences for sales growth, while we consistently find that they do not underperform in terms of profitability, our study provides no support for female underperformance given differences in preferences.
Keywords: D21; D92; J16; L11; M13; 330; Entrepreneurship; Entrepreneurial performancce; Female Entrepreneurs; Female underperformance; Gender economics; Small business growth; Women business owners; Frauen; Entrepreneurship-Ansatz; Unternehmenserfolg; Schweden